Chromosome Study of Slender Walking Catfish (Clarias nieuhofii) and African Catfish (C. gariepinus) F1 Hybrid: Revealed by Conventional Staining and Ag-NOR Banding Techniques - Saowakoon, Samnao; Machoo, Nisa (Food Agricultural Sciences and Technology, 2021)
The hybrid catfishes Clarias nieuhofii (♀) × C. gariepinus (♂) were cytogenetically studied using conventional staining and Ag-NOR banding techniques, with the aim to reveal the chromosome complement and chromosome marker of the hybrid. Specimens were kindly provided by faculty of Agricultural Technology, Songkhla Rajabhat University, Songkhla, Thailand. Mitotic chromosomes were prepared from kidney follow that of the standard protocol. The result showed that hybrid catfishes had chromosome diploid of 2n=61. An intermediate chromosomal pattern incorporating those of the parental species was found in the probable hybrid, confirming its interspecific origin. NORs were observed in one large submetacentric pair and one small subtelocentric pair. The number of diploid chromosome, chromosomal morphology and NOR locations are being cytogenetic evidence to prove that a hybrid occurred from C. nieuhofii × C. gariepinus.